2010
DOI: 10.1098/rspa.2010.0331
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds averaged Navier–Stokes modelling of long waves induced by a transient wave group on a beach

Abstract: This paper presents the numerical modelling of the cross shore propagation of infragravity waves induced by a transient focused short wave group over a sloping bottom. A dataset obtained through new laboratory experiments in the wave flume of the University of Cantabria is used to validate the Reynolds averaged Navier-Stokes type model IH-2VOF. A new boundary condition based on the wave maker movement used in the experiments is implemented in the model. Shoaling and breaking of short waves as well as the enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 31 publications
11
64
0
2
Order By: Relevance
“…Another approach for simulating breaking waves is the application of numerical models based on the Reynolds-averaged Navier-Stokes (RANS) equations (e.g. Lin and Liu, 1998), which have been validated for the study of breaking waves (Torres-Freyermuth et al, 2007;PedrozoAcuna et al, 2010) and low-frequency wave transformation Lara et al, 2011) in different environments. In a recent study by Lanza et al (2012), the RANS model application over fringing reefs demonstrates its potential for describing reef hydrodynamics.…”
Section: A Torres-freyermuth Et Al: Modelling Water Levels In Puertmentioning
confidence: 99%
“…Another approach for simulating breaking waves is the application of numerical models based on the Reynolds-averaged Navier-Stokes (RANS) equations (e.g. Lin and Liu, 1998), which have been validated for the study of breaking waves (Torres-Freyermuth et al, 2007;PedrozoAcuna et al, 2010) and low-frequency wave transformation Lara et al, 2011) in different environments. In a recent study by Lanza et al (2012), the RANS model application over fringing reefs demonstrates its potential for describing reef hydrodynamics.…”
Section: A Torres-freyermuth Et Al: Modelling Water Levels In Puertmentioning
confidence: 99%
“…The correlation peak for the reflected waves is at τ 2 , and as the reflected signal occurs first at B the lag or travel time is negative in the cross-correlation plot. Those peaks have been observed in laboratory and numerical experiments (Janssen et al, 2003, Lara et al, 2010. In the field, this picture is not always clear, but according to the results obtained in the present study they are still significant for some conditions.…”
Section: Infragravity Wave Data Analysissupporting
confidence: 49%
“…It is the easiest technique to be implemented considering that it is based on linear shallow water theory (as presented in equation 5). Previous works on other numerical models Torres et al (2010), Lara et al (2011) have shown that it works relatively well even when used for waves outside the shallow water regime.…”
Section: Boundary Conditionsmentioning
confidence: 99%